Preliminary Assessment of Chemical Characteristics of Dissolved Organic Carbon in Surface Waters of the Hulugou Watershed,Qinghai-Tibetan Plateau - ZHOU Min; SUN Ziyong; ZHENG Chunmiao; ZHENG Yan (2013)
Climate warming induced permafrost melting has begun to exert considerable impact on watershed hydrology,including water quality.The concentration and characteristics of dissolved organic carbon(DOC)in stream water are expected to respond or may even be sensitive indicators of such changes.Optical properties of the light absorbing or chromophoric fraction of DOC can provide information on the amount,source,and quality of Climate warming induced permafrost melting has begun to exert considerable impact on watershed hydrology,including water quality.The concentration and characteristics of dissolved organic carbon(DOC)in stream water are expected to respond or may even be sensitive indicators of such changes.Optical properties of the light absorbing or chromophoric fraction of DOC can provide information on the amount,source,and quality of 中国地质学会、美国地质学会 3 Vol.87